Brain network activation (bna) analysis as a biomarker for concussion assessment and management. Issue 11 (25th May 2017) - Reches, Amit; Kutcher, Jeffrey; Elbin, RJ; Or-ly, Hadas; Greer, Jacob; McAllister, DJ; Kontos, Anthony P
Abstract : Objective: There is a need for objective biomarkers to help identify concussion, monitor recovery, and assist clinicians in managing patients. Brain network activation (BNA) analysis is a high-density, multi-channel mapping and analysis technology that uses a subject's event-related potentials to describe cortical activity and functional connectivity. The current study describes BNA analysis in three patients who sustained a concussion. Design: Case series. Setting: Three primary concussion clinics in the USA. Participants: Three subjects who sustained a concussion, ages 16 to 31 years, one male and two females. Outcome measures: BNA score, a measure of the how similar the subject's brain activity was to a normative population (0%=no similarity, 100%=complete similarity); Patient-reported symptoms. Main results: In the acute time period following their concussion, each patient's BNA score decreased to 10–20%, indicating little similarity to brain activity and connectivity of normative populations. The immediate reduction in BNA score during this time period was accompanied by concussion-related symptoms reported by each patient. In a longitudinal BNA analysis, the patients' BNA scores returned to within a normal range between 23 and 30 days following concussion. In contrast, the recovery trajectory of patients' symptoms varied, with one patient no longer reporting symptoms of concussion though the BNA score was still outside the normal range, while another patient continued to report symptoms of concussion after the BNA score returned to the normal range. Conclusions: BNA analysis could provide a biomarker to augment current approaches to assessing and managing patients with concussion. Competing interests: AR and HO are employed by ElMindA, the company that manufacturers the BNA technology. APK acts as a consultant for ElMindA, the National Basketball Association, National Hockey League Players' Association, National Football League Players' Association, and US Ski and Snowboard Association. JK, RJE, JG, and DJM None.